2009
DOI: 10.1007/s10705-009-9269-4
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of groundwater N2O at the soil surface and its contribution to total N2O emissions

Abstract: Production and accumulation of the major greenhouse gas nitrous oxide (N 2 O) in surface groundwater might contribute to N 2 O emissions to the atmosphere. We report on a 15 N tracer study conducted in the Fuhrberger Feld aquifer in northern Germany. A K 15 NO 3 tracer solution (60 atom%) was applied to the surface groundwater on an 8 m 2 measuring plot using 45 injection points in order to stimulate production of 15 N 2 O by denitrification and to detect its contribution to emissions at the soil surface. Samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 38 publications
5
39
1
Order By: Relevance
“…The contribution of groundwater N 2 O to surface fluxes is dependent on multiple environmental factors such as soil moisture and texture that influence the production and consumption of N 2 O as it diffuses upwards through the vadose zone (von der Weymann et al 2009). N 2 O fluxes from IR positions were inversely related to groundwater depth in shallow wells (r = -0.49, P \ 0.001, Figure S1; Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of groundwater N 2 O to surface fluxes is dependent on multiple environmental factors such as soil moisture and texture that influence the production and consumption of N 2 O as it diffuses upwards through the vadose zone (von der Weymann et al 2009). N 2 O fluxes from IR positions were inversely related to groundwater depth in shallow wells (r = -0.49, P \ 0.001, Figure S1; Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…McPhillips et al (2015) found that longer residence time of groundwater flow increased denitrification rates while promoting lower N 2 O:N 2 ratios. Some studies have concluded that N 2 O fluxes from groundwater are not an appreciable contribution to the atmosphere (Clough et al 1999;Weymann et al 2009). During diffusion through the saturated zone, N 2 O may be further reduced to N 2 , reducing the potential for N 2 O emissions from groundwater to the atmosphere.…”
Section: Anthropogenic Activity Has Drastically Altered the Global Nimentioning
confidence: 99%
“…Weymann et al (2009) demonstrated that groundwater N 2 O contributes negligibly to the flux of N 2 O to the atmosphere from surface soils. Similarly, we found that groundwater delivery of N 2 O makes up a small portion of total biogenic N 2 O emissions (15 % on average) from strongly gaining agricultural streams where groundwater would be expected to be an important source compared to other aquatic systems.…”
Section: N 2 O Emissionsmentioning
confidence: 99%
“…Since N 2 O concentrations in the unsaturated zone above the groundwater table are low, i.e. similar to ambient N 2 O concentrations (von der Weymann et al, 2009), we want to emphasize that the described N 2 O accumulation is a result of the in situ production in the groundwater. In contrast, the unsaturated zone was identified as an N 2 O source for British limestone aquifers (Mühlherr and Hiscock, 1998).…”
Section: Field Measurements Reveal the Zones Of Denitrification And Nmentioning
confidence: 99%